Ecological indicators and phytoremediation efficiency for heavy metal-polluted aquatic ecosystems - Mohd Hatta, Farah Ayuni; Mat Ali, Qurratu Aini; Othman, Rashidi; Wan Sulaiman, Wan Syibrah Hanisah; Mohd Latiff, Nur Hanie; Ramya, Razanah (Nova Science Publishers, Inc., 2024)
Climate change, urbanisation, overuse of resources, and poor waste management have caused water scarcity and pollution in 40% of the world. Heavy metals (HMs) are among the toxic substances responsible for global pollution. HMs can easily accumulate and cause great harm to both human health and the environment. The most prevalent HMs in the aquatic ecosystem are Zn, Cu, Pb, Cd, Hg, Ni, and Cr. Some of these HMs are crucial trace metals for living things, but in higher amounts, they become hazardous. Others, like Pb and Cd, are poisonous while having no biological purpose. The occurrence of aquatic plants is related to water chemistry. The utilisation of these plant species or communities as indicators or biomonitors has been a primary goal in assessing water quality. Conventional HMs clean-up techniques are frequently expensive, time-consuming, harmful to the environment, and ineffective. To restore contaminated areas, phytoremediation has emerged as a technology that provides affordable and ecologically sustainable solutions. Aquatic plant species are known as excellent phytoremediators because they can accumulate substantially higher HM concentrations exhibiting no toxicity. Therefore, this chapter will address phytoremediation by aquatic plants to restore HMs-polluted aquatic ecosystems. Submerged species have shown an exceptional ability to accumulate HMs in their whole bodies. Emergent normally facilitates the removal of HMs through retention and uptake through their respective tissues. Whereas floating aquatic plants do not increase adsorption through the substrate, but they facilitate adsorption to the plant biomass.